A comparison of Percutaneous femoral access in Endovascular Repair versus Open femoral access (PiERO): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Vierhout, Bastiaan; Saleem, Ben; Ott, Alewijn; van Dijl, Jan; de Kempenaer, Ties; Pierie, Maurice; Bottema, Jan; Zeebregts, Clark
Abstract Background Access for endovascular repair of abdominal aortic aneurysms (EVAR) is obtained through surgical cutdown or percutaneously. The only devices suitable for percutaneous closure of the 20 French arteriotomies of the common femoral artery (CFA) are the Prostar™ and Proglide™ devices (Abbott Vascular). Positive effects of these devices seem to consist of a lower infection rate, and shorter operation time and hospital stay. This conclusion was published in previous reports comparing techniques in patients in two different groups (cohort or randomized). Access techniques were never compared in one and the same patient; this research simplifies comparison because patient characteristics will be similar in both groups. Methods/Design Percutaneous access of the CFA is compared to surgical cutdown in a single patient; in EVAR surgery, access is necessary in both groins in each patient. Randomization is performed on the introduction site of the larger main device of the endoprosthesis. The contralateral device of the endoprosthesis is smaller. When we use this type of randomization, both groups will contain a similar number of main and contralateral devices. Preoperative nose cultures and perineal cultures are obtained, to compare colonization with postoperative wound cultures (in case of a surgical site infection). Furthermore, patient comfort will be considered, using VAS-scores (Visual analog scale). Punch biopsies of the groin will be harvested to retrospectively compare skin of patients who suffered a surgical site infection (SSI) to patients who did not have an SSI. Discussion The PiERO trial is a multicenter randomized controlled clinical trial designed to show the consequences of using percutaneous access in EVAR surgery and focuses on the occurrence of surgical site infections. Trial registration NTR4257 10 November 2013, NL44578.042.13.